Design engineer's case studies and examples (CRC Press, 2014)
Written for engineers who are contemplating moving towards the Eng.Tech, this book covers topics they are likely to encounter in their professional career and gives solutions to typical problems that may arise in mechanical design. Topics include stress calculations, basic shaft design, beams under bending, keys and spline strength calculations, columns and struts, gears, introduction to material selection, and conversions and general tables